2012
DOI: 10.1111/j.1365-2915.2012.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Host preferences of PalaearcticCulicoidesbiting midges: implications for transmission of orbiviruses

Abstract: Feeding success depends on host availability, host defensive reactions and host preferences. Host choice is a critical determinant of the intensity at which pathogens are transmitted. The aim of the current study was to describe host preferences of Palaearctic Culicoides species (Diptera: Ceratopogonidae) Latreille using traps baited with the five different host species of poultry, horse, cattle, sheep and goat. Collections were carried out nightly in July and August 2009 in western France with three replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…Van der Rijt et al (2008) also reported that host infectious status affects host location by vectors, as suggested by Torres-Estrada and Rodriguez (2003) and Lacroix et al (2005). C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012). While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Van der Rijt et al (2008) also reported that host infectious status affects host location by vectors, as suggested by Torres-Estrada and Rodriguez (2003) and Lacroix et al (2005). C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012). While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Most species of the genus Culicoides are known to be either mammalophilic (Hair and Turner, 1968;Foxi and Delrio, 2010;Garros et al, 2011;Calvo et al, 2012) or ornithophilic (Bennett, 1960;Hair and Turner, 1968;Garvin and Greiner, 2003;Mullens et al, 2006; Martinez-de la Puente et al, 2009;Votypka et al, 2009;Foxi and Delrio, 2010;Cerny et al, 2011), although some feed on reptiles or frogs. In a previous study using animal-baited traps, horses were found to be the most attractive hosts for the three main Palaearctic Culicoides species, including C. obsoletus (Viennet et al, 2013). C. obsoletus followed by Culicoides pulicaris L. 1758 was also the most abundant species found on horses (Van der Rijt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations